World Haptics 2009 - Third Joint EuroHaptics Conference and Symposium on Haptic Interfaces for Virtual Environment and Teleoper 2009
DOI: 10.1109/whc.2009.4810811
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual coding of haptic data in time-delayed teleoperation

Abstract: In telepresence and teleaction systems the haptic communication channel plays a central role. As it closes a global control loop any introduced communication delay possibly destabilizes the system and impairs the performance. The scattering theory is known to solve these stability issues by transmitting wave variables instead of haptic signals, i.e. force and velocity, over the communication channel. For stability and performance additionally high packet rates are required stressing the underlying network reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Then, a perceptual deadband coding scheme with a JND of 10% is applied on the so-call locally computed wave-variables (LCWV) to reduce the packet rate. In our work, the environment is more complex and the communication delay is higher than in [42] (arbitrary 3-dimensional object surface vs. 1-dimensional planar surface and round-trip delay: 1000ms vs. 30ms). With such a complex case, our pcbMMT method can also significantly reduce the packet rate without degrading the system stability and transparency as the passivity-based haptic data reduction method described in [42] does.…”
Section: B2 Data Reductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Then, a perceptual deadband coding scheme with a JND of 10% is applied on the so-call locally computed wave-variables (LCWV) to reduce the packet rate. In our work, the environment is more complex and the communication delay is higher than in [42] (arbitrary 3-dimensional object surface vs. 1-dimensional planar surface and round-trip delay: 1000ms vs. 30ms). With such a complex case, our pcbMMT method can also significantly reduce the packet rate without degrading the system stability and transparency as the passivity-based haptic data reduction method described in [42] does.…”
Section: B2 Data Reductionmentioning
confidence: 93%
“…We compare the result with a previous work for haptic data reduction in delayed teleoperation systems. In [42], the author uses the wave-variable approach [5] to enable a stable teleoperation system in the presence of communication delays. Then, a perceptual deadband coding scheme with a JND of 10% is applied on the so-call locally computed wave-variables (LCWV) to reduce the packet rate.…”
Section: B2 Data Reductionmentioning
confidence: 99%
“…In [26], [27], the PD approach was combined with the WV control scheme (PD+WV). The authors of [26] applied the PD approach directly on the wave variables and found the subjectively best deadband parameter (DBP) for an interaction with a rigid wall in the presence of a 100 ms round-trip communication delay.…”
Section: Combined Solutionsmentioning
confidence: 99%
“…Psychophysical studies indicate that the loss of information induced by the algorithm can be considered imperceivable. Teleoperation systems with timedelay are studied in [7], and perceptual-coding in time-delayed systems is presented in [8]. Stability of the global control loop is challenging as long as information is removed from it.…”
Section: Fig 1: Multimodal Telepresence and Teleaction Systemmentioning
confidence: 99%